Kegiatan Bersih Kampus oleh Mahasiswa Universitas Sunan Giri Surabaya dengan Kepedulian Lingkungan yang Sehat - Febrian Dirgantara; Diego Fathqurahman Mustaqim; Rommy Hardyansah; Didit Darmawan; Wakid Evendi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the strategies implemented by the Environmental Awareness Student Association in fostering environmentally responsible character among students at Universitas Sunan Giri Surabaya. The research employs a descriptive qualitative approach within the framework of Participatory Action Research (PAR), as character formation requires active involvement between researchers and organizational members in planning, implementing, observing, and reflecting on each action. Data were collected through in-depth interviews, participatory observations, and documentation consisting of photos, activity notes, and environmental program archives. The data were analyzed through stages of reduction, data display, and conclusion drawing, following the continuous PAR cycle. The results indicate that the strategies for developing environmentally responsible character are carried out through several approaches: (1) strengthening solidarity among members; (2) modeling environmentally responsible behavior; (3) providing systematic education on the importance of environmental stewardship; and (4) organizing work programs focused on environmental care. The findings also show that the cognitive aspect of members improved through scheduled educational activities, although the modeling aspect in daily practice particularly within the secretariat remained less optimal. Meanwhile, members demonstrated strong motivation during field programs and outdoor activities. Overall, the study emphasizes that sustainable strategies based on PAR can effectively support the development of environmentally responsible character when reinforced by consistent exemplary practices and a supportive organizational environment.